Breastfeeding practices among postpartum mothers in Maharaj Nakhon Si Thammarat Hospital, Muang District, Nakhon Si Thammarat Province - Chutchaporn Hengsiri (Chulalongkorn University, 2003)
Breast milk is the most appropriate nutrition for infants. Breast milk also benefits infants, mothers, and society, so breastfeeding is most highly regarded. However, even if breastfeeding has continuously been promoted, the rate and duration of breastfeeding has constantly declined. The objectives of the present study were to investigate duration and rate of breastfeeding in the first four months after child delivery and to determine factors related to exclusive breastfeeding during the first four months of postpartum mothers who gave birth at Maharaj Nakhon Si Thammarat Hospital. The subjects were 400 postpartum mothers who took their four-to-six-month-old infants to the ten Primary Care Units under the network of Maharaj Nakhon Si Thammarat Hospital to receive vaccination between July 1 and August 31, 2003. Data were gathered by means of interview questionnaires, focus group discussion, and observation of public health officials support of breastfeeding during different phases. The PRECEDE Framework was applied as the conceptual framework of the present study. Data were analyzed in terms of frequency distribution, and Chi-square test was used. The findings revealed that only 20.5% of the subjects exclusively breastfed their infants for four months and that the period of highest rate of exclusive breastfeeding was one month or less (26.5%). Also, the largest group of subjects, or 35.6%, stopped breastfeeding at one month after delivery or less with the following reasons: having to return to work outside the house (37.7%) and not having enough lactation (33.7%). In addition, the predisposing factors which were statistically significantly associated with exclusive breastfeeding for at least four months at the 0.05 and <0.001 levels were mothers occupation, place of work, and intention to breastfeed. The enabling factors which were statistically significantly related to breastfeeding for at least four months at the .05 and < .001 levels were experience with breastfeeding, characteristic of nipples, infants’ health problems during the first four months, current weight of infants, and type of milk/formula received during hospital stay. However, there was no statistically significant relationship between the reinforcing factor and exclusive breastfeeding for at least four months. The findings of the present study could be used in proposing the project to promote readiness of mothers and relatives to encourage exclusive breastfeeding for at least four months at Maharaj Nakhon Si Thammarat Hospital to prevent and help solve problems and obstacles after hospital discharge and to increase postpartum mothers chance of successful breastfeeding during the first four months.